1997
DOI: 10.1016/s0741-5214(97)70042-9
|View full text |Cite
|
Sign up to set email alerts
|

Fate of the proximal aortic cuff: Implications for endovascular aneurysm repair

Abstract: One third of all patients who survive AAA repair experience significant dilatation of their proximal aortic cuff over time. Proximal dilatation is rare but not absent in patients who have smaller initial aortic cuff diameters. This dilatation rarely causes problems after conventional suture fixation, but the long-term implications of cuff dilatation after endoluminal repair are unclear. Our findings suggest that endovascular aortic prostheses that have the ability to continue to self-expand many years after im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
89
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(93 citation statements)
references
References 13 publications
3
89
0
1
Order By: Relevance
“…Significant modification in the proximal aortic neck has been demonstrated after surgical treatment of abdominal aortic aneurysm (AAA) [1,2]; however, evidence of dilatation at the level of the supraand infrarenal aortic neck is still controversial [3,4,5,6], as well as its pathogenesis and etiology. In a recent study, Badran et al concluded that the proximal neck dilates in one-third of patients, mostly in the first 2 years after EVAR [7].…”
Section: Introductionmentioning
confidence: 99%
“…Significant modification in the proximal aortic neck has been demonstrated after surgical treatment of abdominal aortic aneurysm (AAA) [1,2]; however, evidence of dilatation at the level of the supraand infrarenal aortic neck is still controversial [3,4,5,6], as well as its pathogenesis and etiology. In a recent study, Badran et al concluded that the proximal neck dilates in one-third of patients, mostly in the first 2 years after EVAR [7].…”
Section: Introductionmentioning
confidence: 99%
“…24,25 The infrarenal aorta in patients with small untreated aneurysms or after open repair can enlarge at a rate of up to 0.57 to 0.58 mm/y. 31,32 This study used the suprarenal aorta as an internal control to evaluate the changes in the infrarenal aorta in the two study groups.…”
Section: Discussionmentioning
confidence: 99%
“…As it is possible to notice, increment in stress is linked to a general reduction of the thickness. Thus by establishing a threshold value of 0,45 MPa, it can be argued that in an aneurysm's cap, subject to a inner static pressure of 19.000 MPa and of thickness 0,8 mm, the equivalent Von Mises stress reaches 0,45 MPa, recognised as failure value.…”
Section: Discussionmentioning
confidence: 99%
“…Also proximal neck dilatation can be identified as a possible cause of risk as contributes to the aortic weakening [19]. So many causes can play an important rule in aneurysms generation and degeneration or stabilization as reported in literature [20] and a not scientific proved criterion can give guaranties about the necessity to operate or not [21].…”
Section: Introductionmentioning
confidence: 99%